Correlation between human factors and the prevention of disasters - Barry, David L. (NATO science for peace and security series. Human and societal dynamics, 2012)
The nuclear disaster at the Chernobyl power plant, devastating floods, landslides, droughts, the erosion of tailings dams and desertification are just some of the natural and manmade disasters which have afflicted the Ukraine and neighboring countries in recent years. It is therefore entirely appropriate that the NATO Advanced Research Workshop (ARW), Correlation between Human Factors and the Prevention of Catastrophes, was held in Dnipropetrovsk, Ukraine in September 2011. This book presents the proceedings of the ARW, which analyzed accumulated European theoretical knowledge and practical ex.